2020
DOI: 10.1038/s41467-020-19379-4
|View full text |Cite
|
Sign up to set email alerts
|

Surface-controlled reversal of the selectivity of halogen bonds

Abstract: Intermolecular halogen bonds are ideally suited for designing new molecular assemblies because of their strong directionality and the possibility of tuning the interactions by using different types of halogens or molecular moieties. Due to these unique properties of the halogen bonds, numerous areas of application have recently been identified and are still emerging. Here, we present an approach for controlling the 2D self-assembly process of organic molecules by adsorption to reactive vs. inert metal surfaces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 50 publications
7
48
0
Order By: Relevance
“…Similar bending halogen bond was reported by Ebeling et al 36 We infer that the steric hindrance of two adjacent H-atoms hinders the alignment of Br-atom with two N-atoms of a pyrazine ring.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Similar bending halogen bond was reported by Ebeling et al 36 We infer that the steric hindrance of two adjacent H-atoms hinders the alignment of Br-atom with two N-atoms of a pyrazine ring.…”
Section: Resultssupporting
confidence: 90%
“…In recent years, several reports have shown that STM with CO-tip is also able to unravel the internal atomic structure of a single molecule. [33][34][35] The intermolecular force of triangular halogen bonds has also recently been studied by nc-AFM and STM, 36 and the bright lines appear at positions where the triangular halogen bond form at STM images. 13 The bright lines (or image contrast) are thought to originate from the interacting electrons of intermolecular bonds, while others propose that bright lines are caused by the bending of the CO molecule.…”
Section: Introductionmentioning
confidence: 99%
“…However, the majority of these studies have been focused on planar or nearly-planar molecular structures. In addition, on-surface molecular assemblies investigated to date mainly involve a limited category of non-covalent interactions, such as halogen bond [5,15,16] or hydrogen bond interactions. [17] Molecularlevel insights into complex three-dimensional (3D)-like assemblies with manifold noncovalent interactions remain largely unexplored [18].…”
Section: Introductionmentioning
confidence: 99%
“…S7c) and at a distance of about 3.2 Å from one another. The driving force for such self-assembly may thus be either the formation of halogen bonds, [25,26] or the coordination through a gold atom. For the former to be attractive, C-Br bonds require a certain angular offset, whereas the latter requires a surface atom or adatom to be coordinated to the halogens.…”
Section: Resultsmentioning
confidence: 99%